Cultural History of Indian Arts with Subcontinent: Exploring the Influence of Cultural Diplomats in Indian Arts (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The role of these cultural diplomats was significant in contributing to the better sociocultural understanding and building relationship between people of different faiths, sects and regions. Bachhofer provided a rigorous framework of stylistic analysis, which included details of individual forms and overall composition. While he was trained in Western art history, he was also sensitive to the distinctiveness of Indian art. The art of Indian subcontinent is idealistic in nature with strong traces of different cultures and civilizations in it. It is evident from the history that the cultural diplomats in the region were the invaders, warriors that brought the cultural diffusion through hard power but along with them there were a great number of soft power promoters as artists, suifs, poets, musicians, and story tellers. The role of these cultural diplomats was significant in contributing to the better sociocultural understanding and building relationship between people of different faiths, sects and regions.